POTENTIAL ANTIBACTERIAL EXTRACTS OF MANGROVE GENUS AVICENIA ROOT AND LEAVES FROM KOMBI BEACH MINAHASA - Masje Wurarah; Devitha Kalitouw; Raflen Aril Gerungan (Universitas Negeri Manado, 2021)
This study aimed to obtain the phytochemical content of the crude extract of leaves and roots of Avicenia spp from Kombi Beach Minahasa. Obtaining data on the activity of inhibiting the growth of infective microbes on external wounds of crude extract of leaves and roots of Avicenia spp from Kombi Beach, Minahasa. To determine the concentration of minimum growth inhibition of crude extract of leaves and roots of Avicenia spp from Kombi Beach, Minahasa. Knowing the crude extract (crude extract) leaves and roots of Avicenia spp originating from the Minahasa Kombi Beach is bactericidal or bacteriostatic. This research consisted of extraction, phytochemical analysis and antibacterial activity test. The results showed that the dominant secondary metabolites in the root and leaf extracts were alkaloids, flavonoids, saponins and tannins. The chloroform extract inhibited the growth of bacteria in infected wounds more than the ethanol and n-hexane extracts, at concentrations of 15 and 30 ppm for the test solution of ethanol extract with an inhibitory diameter of < 7 mm and a concentration of 50 ppm with an inhibitory diameter of > 10 mm indicating that the high bioactive activity antibacterial.